Trimetazidine MR effects on heart remodeling in stable coronary heart disease patients - E. M. Khurs; Yu. A. Zinovyeva; A. V. Poddubnaya; I. I. Kotsuba; O. G. Smolenskaya (Кардиоваскулярная терапия и профилактика)
Aim. To study trimetazidine MR effects on left ventricular (LV) remodeling in stable coronary heart disease (CHD) patients with completely controlled effort angina and arterial hypertension (AH), who received combined treatment. Material and methods. In total, 114 individuals were examined: Group I – 65 healthy volunteers (mean age 31,38 years); Group II - 49 untreated CHD and AH patients (mean age 62,32 years). All participants underwent transthoracic echocardiography, with calculation of systolic and diastolic spherical index, remodeling index (RI), systolic and diastolic myocardial stress (MSs, MSd), LV myocardial mass index, LV relative wall thickness (RWT). Results. After three months of combined, four-component treatment, clinical stabilization was not associated with significant changes in LV remodeling, only MSs reduced significantly after adding Preductal MV to the treatment. In stable good clinical status, no obvious clinical dynamics, and unchanged ejection fraction, structural and functional cardiac parameters improved substantially, with reduction (р<0,00001) in MSs (145,68±11,35 and 124,51±7,89); MSd (160,72±16,78 and 156,24±12,11), end-diastolic pressure (14,81±3,16 and 11,9±1,91 mm Hg), end-diastolic LV wall strain (1967,33±337,27 and 1519,99±224,74 dyne/cm2), as well as with increase in RI (93,72±8,48 and 100,87±9,74). LV diastolic function parameters improved, NYHA functional class reduced. Conclusion. Trimetazidine MR beneficial effects on myocardial elasticity, contractility, and remodeling were demonstrated. The medication can be used as an anti-remodeling agent in combined CHD treatment.